Empowering children through art and expression : culturally sensitive ways of healing trauma and grief - St. Thomas, Bruce, 1948- (Jessica Kingsley Publishers, 2007)
Empowering Children through Art and Expression examines the successful use of arts and expressive therapies with children, and in particular those whose lives have been disrupted by forced relocation with their families to a different culture or community. The book explores how children express and resolve unspoken feelings about traumatic experiences in play and other creative activities, based on their observations of peer support groups, outreach programs and through individuals' own accounts. The authors argue that such activities in a safe context can be both a means of expressing trauma.